Application of broadband acoustic resonance dissolution spectroscopy (BARDS) to the gas release behaviour during rehydration of milk protein isolate agglomerates. (July 2019) - Wu, Shaozong; Fitzpatrick, John; Cronin, Kevin; Ahmed, M. Rizwan; Fitzpatrick, Dara; Miao, Song
Abstract: The BARDS technique was applied in this study to acoustically assess the rehydration behaviour of milk protein isolate (MPI) agglomerates and to compare with regular MPI powder. The results showed that BARDS has potential to monitor the rehydration behaviour of agglomerates. The greater porosity (>70%) of agglomerated powders introduced more compressible gas into the water. The BARDS profile showed that there was faster initial gas release from the agglomerates, indicating better wetting and dispersion ability of the agglomerates with shorter tM (time of maximum gas volume in solution). At 0.10% powder addition, agglomerated MPI reached tM within 109 s, which was significantly less than the control MPI at 140 s. MPI with lactose binder (MPI-L) had a tM of 80 s at 0.10% powder addition and, larger size MPI-L had a tM of 60 s. At 0.20% and 0.30% powder addition, more time was required to wet and disperse the powders. Highlights: BARDS successfully monitored rehydration of MPI agglomerates. BARDS showed that MPI agglomerates wetted more quickly than MPI powder. BARDS showed that agglomerate size and binder type influenced rehydration. Dissolution of MPI agglomerates was rate-limited by dissolution of primary MPI particles.